Muhammadiyah's Tajdīd and Sufism between Purification and Modernization - Zubair Zubair; Muhammad Farkhan; Zakiya Darojat; M Agus Suriadi; Masri Mansoer; Abdul Fattah (Insaniyat : Journal of Islam and Humanities, 2023)
This article aims to reveal the purification or modernization performed by Muhammadiyah in Sufism, especially concerning the practical mysticism in sufi order and philosophical mysticism on the concepts of ittihād, hulūl, and wahdat al wujūd. The research data is gathered from the official document Muhammadiyah records, such as fatwas of Muhammadiyah's Majlis Tarjih and Tajdid, Hamka's thoughts and AR Fakhruddin’s performance as former leaders of Muhammadiyah. This study uses content analysis to determine the position of Muhammadiyah's views on the early Sufi. The result showed that tajdīd performed by Muhammadiyah is called purification and it harmonious with modern life. It differs with the meaning and practices of early Sufism.  Muhammadiyah's position towards tarīqa is positive as long as the understanding and practice of Islam are derived from the guidance of the Qur'an and valid Sunnah. As for the concepts of ittihād, hulūl and wahdat al-wujūd, Muhammadiyah rejects them because there is an element of equating God with humans or pantheism, which has no basis in the Qur'an and Sunnah. This rejection is in line with what has been done by early Sufism scholars such as al-Sarrāj, al-Juwairī, al-Syahrastānī, and al-Kalabāżī.